Correction: Three-season evaluation of partial root zone drying as a water-saving strategy in commercial Chilean vineyards: effects on Carménère and Merlot - Daniel Knopp; Pilar M. Gil; Daniela Cea; Claudia Bonomelli; Natalia Brossard; Edmundo Bordeu; Alejandra Zúñiga; Héctor Ibarra; Felipe Torres; Camila Poblete; Diego Rodríguez (Irrigation Science, 2026)

Integrin inhibition differentially remodels vascular networks in lung metastases driven by vessel co-option or angiogenesis - Laura Marcos-Zazo; Iván Carrera-Aguado; Jesús Gómez-Escudero; Patricia Berlana-Galán; Irene Torre-Cea; Elena Guerra-Paes; Celia Redondo-Gonzalez; Juan Sánchez-Mateos; Daniel Cáceres-Calle; Óscar Maiques; Miguel Pericacho; Susana Fraile; et al. (Angiogenesis, 2026)
Tumor progression depends on an adequate blood supply to sustain oxygen and nutrients delivery. While tumor angiogenesis involves the formation of new blood vessels from pre-existing ones, vessel co-option represents a non-angiogenic vascularization strategy whereby tumor cells utilize pre-existing host vessels. Co-opted vessels have been considered refractory to anti-angiogenic therapies, and pharmacological modulation of co-opted vessels remains limited. In this study, we investigate the effects of low-dose cilengitide on tumor vascular remodeling in vessel co-option and angiogenic metastatic models. Our results reveal that cilengitide exerts distinct vascular effects depending on the mode of tumor vascularization. In vessel co-option-driven tumors, cilengitide treatment is associated with the remodeling of the co-opted vasculature into a more organized normalized vascular network, characterized by an increased number of functional blood vessels and enhanced vascular barrier integrity. In contrast, in angiogenic-driven tumors, cilengitide treatment promotes an expansion of the vascular network consistent with augmented, but structurally immature angiogenesis. Importantly, vascular remodeling in vessel co-option metastases is accompanied by enhanced blood vessel perfusion and reduced hypoxia, which correlates with enhanced responsiveness to chemotherapy. Conversely, in angiogenic metastases, the vascular network induced by low-dose cilengitide fails to support immunocompetent microenvironmental features and is associated with increased chemotherapy resistance. This study provides the first evidence that co-opted vasculature can be therapeutically targeted via integrin inhibition, suggesting vascular normalization remodeling as a potential strategy to overcome resistance in tumors undergoing vessel co-option.

Three-season evaluation of partial root zone drying as a water-saving strategy in commercial Chilean vineyards: effects on Carménère and Merlot - Daniel Knopp; Pilar M. Gil; Daniela Cea; Claudia Bonomelli; Natalia Brossard; Edmundo Bordeu; Alejandra Zúñiga; Héctor Ibarra; Felipe Torres; Camila Poblete; Diego Rodríguez (Irrigation Science, 2026)

Fire–climate–human dynamics over the last 1800 years in the mesic Araucaria‐Nothofagus forests - Alejandra Martel‐Cea; Ana M. Abarzúa; Mauro E. González; Leonora Jarpa; Marjorie Hernández (Journal of Biogeography, 2024)
Aim Few palaeoenvironmental studies have been performed in Araucaria‐Nothofagus forests, which are highly vulnerable to ongoing threats from climate change and anthropogenic activities. The primary goal of this work is to reconstruct past environmental changes related to fire disturbances over the last 1800 years in Tolhuaca National Park (TNP), Chile. Location TNP, Araucanian region (38.2°S; 71.8°W), Northwestern Patagonia, Chile. Taxa Araucaria araucana (Araucariaceae), Nothofagus spp. (Nothofagaceae). Methods We completed charcoal and pollen analyses to create two new palaeoecological records that span 1800 years. We compared the lake‐based reconstruction with the available local tree‐ring fire scar chronologies from the last 430 years. Using these data, we compute forest index changes, biomass burning trends and compare with estimates of archaeological radiocarbon density. We place our inferences with context of published regional palaeoclimatic proxies from the Patagonian‐Andean region. Results Our results showed that fire activity was higher than present between 200 and 1500 CE, with peaks around 200–400 CE and 1100–1500 CE. Periods with high fire activity are associated with reduced forest cover, as Araucaria declined when mixed‐severity fire regime occurred for extended periods. Pollen assemblages suggested a shift from dry to wet climate conditions at 1500 CE, and from 1750 CE onward, the arrival of exotic species reflected the land‐use changes related to forest clearance and transhumance practices. Main Conclusions The palaeoenvironmental reconstructions showed changes in vegetation, fire and climate over the past 1800 years in TNP. Wildfires have been the main disturbance process modifying the vegetation structure in the Araucaria and Nothofagus forests. Since 1750 CE intensive post‐Hispanic land‐use changes (forest clearances by fire and logging) took place in the study area, reducing the native vegetation cover. Climate variability, modulated by SAM‐like and ENSO‐like conditions, influenced the fire activity (availability and flammability of fuels), concomitantly with high archaeological density. The recent (after 2000 CE) increase of catastrophic wildfires may negatively affect the conservation strategies of Araucaria‐Nothofagus forests.

Scaling theories for predicting the viscosity of binary and ternary refrigerant mixtures - Bastián González-Barramuño; Esteban Cea-Klapp; Sebastián Cerda; Ilya Polishuk; Manuel M. Piñeiro; Héctor Quinteros-Lama; José Matías Garrido (International Journal of Refrigeration, 2023)

Major Fusarium species and mycotoxins associated with freshly harvested maize grain in Uruguay - A. del Palacio; B. Corallo; M. Simoens; Jacqueline Cea; I. de Aurrecoechea; I. Martinez; A. Sanchez; S. Stewart; D. Pan (Mycotoxin Research, 2023)

A Robust Method to Update Local River Inundation Maps Using Global Climate Model Output and Weather Typing Based Statistical Downscaling - M. Bermúdez; L. Cea; E. Van Uytven; P. Willems; J.F. Farfán; J. Puertas (Water Resources Management, 2020)

Sorption Parameters of Carbendazim and Iprodione in the Presence of Copper Nanoparticles in Two Different Soils - G. R. Tortella; O. Rubilar; M. Cea; C. Rodríguez-Rodríguez; A. Seguel; J. Parada (Journal of Soil Science and Plant Nutrition, 2019)

Adipocyte proteome and secretome influence inflammatory and hormone pathways in glioma - J. Almeida; J. Costa; P. Coelho; V. Cea; M. Galesio; J. P. Noronha; M. S. Diniz; C. Prudêncio; R. Soares; C. Sala; Rúben Fernandes (Metabolic Brain Disease, 2019)

Abies pinsapo Boiss. Transcriptome Sequencing and Molecular Marker Detection: A Novel Genetic Resources for a Relict Mediterranean Fir - A Pérez-González; M Marconi; I Cobo-Simón; B Méndez-Cea; P Perdiguero; R Linacero; J C Linares; F J Gallego (Forest Science, 2018)

Climate and soil attributes determine plant species turnover in global drylands - Werner Ulrich; Santiago Soliveres; Fernando T. Maestre; Nicholas J. Gotelli; José L. Quero; Manuel Delgado‐Baquerizo; Matthew A. Bowker; David J. Eldridge; Victoria Ochoa; Beatriz Gozalo; Enrique Valencia; Miguel Berdugo; et al. (Journal of Biogeography, 2014)
Aim Geographical, climatic and soil factors are major drivers of plant beta diversity, but their importance for dryland plant communities is poorly known. The aim of this study was to: (1) characterize patterns of beta diversity in global drylands; (2) detect common environmental drivers of beta diversity; and (3) test for thresholds in environmental conditions driving potential shifts in plant species composition. Location Global. Methods Beta diversity was quantified in 224 dryland plant communities from 22 geographical regions on all continents except Antarctica using four complementary measures: the percentage of singletons (species occurring at only one site); Whittaker's beta diversity, β(W); a directional beta diversity metric based on the correlation in species occurrences among spatially contiguous sites, β( R 2 ); and a multivariate abundance‐based metric, β( MV ). We used linear modelling to quantify the relationships between these metrics of beta diversity and geographical, climatic and soil variables. Results Soil fertility and variability in temperature and rainfall, and to a lesser extent latitude, were the most important environmental predictors of beta diversity. Metrics related to species identity [percentage of singletons and β(W)] were most sensitive to soil fertility, whereas those metrics related to environmental gradients and abundance [(β( R 2 ) and β( MV )] were more associated with climate variability. Interactions among soil variables, climatic factors and plant cover were not important determinants of beta diversity. Sites receiving less than 178 mm of annual rainfall differed sharply in species composition from more mesic sites (> 200 mm). Main conclusions Soil fertility and variability in temperature and rainfall are the most important environmental predictors of variation in plant beta diversity in global drylands. Our results suggest that those sites annually receiving c . 178 mm of rainfall will be especially sensitive to future climate changes. These findings may help to define appropriate conservation strategies for mitigating effects of climate change on dryland vegetation.

Using volatile organic compounds to enhance atrazine biodegradation in a biobed system - G. R. Tortella; O. Rubilar; J. Stenström; M. Cea; G. Briceño; A. Quiroz; M. C. Diez; L. Parra (Biodegradation, 2013)

Bioremediation of a Chilean Andisol contaminated with pentachlorophenol (PCP) by solid substrate cultures of white-rot fungi - O. Rubilar; G. Tortella; M. Cea; F. Acevedo; M. Bustamante; L. Gianfreda; M. C. Diez (Biodegradation, 2011)

Parallel activation of Ca2+-induced survival and death pathways in cardiomyocytes by sorbitol-induced hyperosmotic stress - M. Chiong; V. Parra; V. Eisner; C. Ibarra; C. Maldonado; A. Criollo; R. Bravo; C. Quiroga; A. Contreras; J. M. Vicencio; P. Cea; J. L. Bucarey; et al. (Apoptosis, 2010)